Effect of Annealing Temperature on the Li\(^{ + }\) Ionic Conductivity of La\(_{0.67 - x}\)Li\(_{3x}\)TiO\(_{3 }\) - Trong, Le Dinh; Long, Pham Duy; Dinh, Nguyen Nang (Communications in Physics, 2009)
Perovskite La0.67-xLi3xTiO3 with x = 0.10, 0.11, 0.12 and 0.13 were firstly annealed at 800 oC then treated by reactive milling, followed by post-annealing at temperatures from 1100 to 1200oC. The crystalline structure of grain and grain-boundary were characterized by XRD and SEM. The impedance measurements showed that nanocrystalline La0.67-xLi3xTiO3 after being annealed at 1150 oC possessed a grain conductivity as high as 1.3×10-3 S.cm-1. The grain-boundary conductivity was enhanced one order in magnitude after annealing at temperature higher 1100oC and consists of 5.8×10-5 S.cm-1. The results have also showed the limitation of the adiabatic thermal treatment for the improvement of the grain-boundary conductivity and suggested the way to overcome the limitation by rapidly cooling the samples from the high temperature to room temperature.